Exploring the benefits and challenges of indigenous foods in an African context using a case study of community gardens in the Western Cape of South Africa - De Bruin, Francia-Marie (Stellenbosch : Stellenbosch University, 2018)
Thesis (MPhil)--Stellenbosch University, 2018.